O-078 The VALUE study: a qualitative semi-structured interview study of add-on use by patients, clinicians, and embryologists in the UK and Australia. (30th June 2022) - Armstrong, S; Vaughan, E; Lensen, S; Caughey, L; Farquhar, C; Pacey, A; Balen, A; Peate, M; Wainwright, E
Abstract: Study question: Why do patients, clinicians and embryologists opt to use IVF add-ons in fertility treatment? Summary answer: Add-ons offer options, hope and control in a desperate situation. The perceived drivers differ between patients and professionals; however, both feel add-ons offer bespoke care. What is known already: Evidence that add-ons offer clinical advantages for the outcomes of IVF is lacking or insufficient. However, they remain popular in the UK and Australia, with over three-quarters of couples opting to use them. Professionals, clinical societies, and the media have latched onto the ethical aspects of offering non-evidence-based add-ons, often provided at an additional cost to vulnerable patients. Conversely, it has also been suggested that patients are driving add-on use. The VALUE study is the first large qualitative study to include both patients and professionals that explores the drivers behind their use, and how the existing evidence is weighed up. Study design, size, duration: VALUE was a multinational semi-structured interview study in the UK and Australia. The interview schedule was reached through extensive patient and public involvement. Between January and May 2021, recruitment took place via social media advertisement, email invitation from professional societies, and snowballing. A purposive sampling strategy was planned; all eligible participants (25 patients, 25 embryologists, and 24 clinicians) were interviewed via recorded teleconference. Anonymised verbatim transcripts were analysed iteratively, and themes developed inductively. Participants/materials, setting, methods: Patient and professional transcripts were coded separately using the software Dedoose TM Two separate thematic analyses followed. An inductive approach to analysis was adopted, whereby themes emerged from the data, opposed to constructing a pre-conceived coding scheme. Codes were combined into broader themes, and sub-themes, which were discussed, debated, and named. The wider research team then commented upon and debated the themes and sub-themes, which were settled upon by consensus. Main results and the role of chance: Thematic analysis of patient interviews identified five themes: 'vulnerability'; 'power of the trusted professional opinion'; 'role of previous experience'; 'acceptability of add-on'; and 'the evidence doesn't apply to me'. The professional interviews identified five themes: 'Treating desperation'; 'tensions within evidence-based practice'; 'success, not profits'; 'the patient shopper'; and 'potential for harm'. Analysis identified that that people undergoing IVF are vulnerable and opting for non-evidence-based treatments at additional cost because of a sense of desperation following unsuccessful cycles. For patients, utilising add-ons lends hope and a sense of control, with considerations of safety and efficacy being ranked lower than hope. For professionals, add-ons are reasonable given the absence of anything else to add, and allows patients the opportunity to exhaust every avenue. At odds with one-another are the themes regarding who is driving add-on use. Patients describe the power of a professional recommendation, believing it to be in their best interest. For professionals, it's the patients who research and request add-ons, and failing to offer them risks losing patients. The tension between evidence and bespoke care was evident across both analyses, with testimonies being particularly powerful for patients, and for professionals, a belief that add-ons are helpful in the right context. Limitations, reasons for caution: The VALUE study has captured patients and professionals who have volunteered to talk about this particularly contentious area of medicine. Participants are likely to be a motivated group of individuals who may potentially represent those with strong views regarding add-ons. Wider implications of the findings: The theme of desperation runs through VALUE's analyses and whilst we did find that patients drive add-on use, professional opinion for or against add-ons was powerful. Patients want autonomy, but only in the context of informed consent. Trial registration number: https://osf.io/he7tn/